FAMILY PARENTING IN MOTIVATING CHILDREN DURING ONLINE LEARNING - Aula Gita Cahyani; Erik Aditia Ismaya; Nur Fajrie (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The research objective was to determine the parenting styles applied by parents to motivate their children in online learn in Desa Kalipucang Wetan Jepara. This research explained factors that motivated children in family parenting in Desa Kalipucang Wetan Jepara and the form of children’s motivation in family parenting in Desa Kalipucang Wetan Jepara. This research discussed the parents’ parenting styles and its implications for children’s motivation in online learning in. Parenting styles referred to the parental control to provide care for children; in this case, parents educated and guided the child’s personality as well as built knowledge so that the child could grow up according to his developmental age. There were four types of parenting, including permissive, democratic, authoritative, and neglective parenting. Family learning environment was a learning environment that greatly affected the children’s pattern of life. Meanwhile, learning motivation was an encouragement from inside and outside to keep learning so that someone, especially elementary school students, could achieve maximum learning outcomes as a result of high enthusiasm or motivation to learn. Positive parenting would provide a high motivation for children to learn.